Methods of determination of territorial resources in conditions of compacted urban development (using Kyiv as an example) - Bakun, Kateryna; Pleshkanovska, Alla (KNUCA, 2018)
The article highlights the results of the analysis of domestic and foreign experience of application of the applied coatings and a modifiеd typology of roofs based on their geometric and structural features is proposed. The following factors that influence taking the decision on the need and directions of the use of the used roofs are provided. On the basis of the analysis of the dynamics of the normative and actual indicators of urban development, the constant growth of the development density and growth of the lack of territory for greenery and other elements of the population service are proved. The described methods for the determination of the resource potential of urban areas are normative method, comparative and calculation method. A new calculation method for identifying potential territorial resources of micro districts, blocks or individual plots due to the use of exploited roofs in conditions of compacted urban development has been proposed. The mathematical model is based on taking into account the geometric type of the roof, type of historically originated development, its technical condition and the availability of the status of the cultural heritage monument. Coefficients for the calculation of the potential territorial resource have been experimentally determined. Based on the example of Kyiv, using GIS-technologies, a specialized database for identifying a potential territorial resource has been formed. The recommendations for placement on differеnt types of objects on the exploited roofs depending on the frequency of their visit and the cityplanning situation have been provided. The methodical scheme for the determination of a potential territorial resource due to the use of exploited roofs in the development of urban planning, design and land management documentation has been proposed.
Keywords: the exploited roof; potential territorial resource; typology of roofs; typology of the development; mathematical model